To solve the given quadratic equation \(49x^2 = -392x - 784\) using the perfect square trinomial pattern, we first rearrange it into standard form:
\[ 49x^2 + 392x + 784 = 0 \]
Next, we can simplify this equation by dividing all terms by 49 (the coefficient of \(x^2\)):
\[ x^2 + \frac{392}{49}x + \frac{784}{49} = 0 \] \[ x^2 + 8x + 16 = 0 \]
Now, we see that the left-hand side can be expressed as a perfect square:
\[ (x + 4)^2 = 0 \]
To solve for \(x\), we take the square root of both sides:
\[ x + 4 = 0 \]
Thus, solving for \(x\):
\[ x = -4 \]
The solution to the given quadratic equation is:
\[ x = -4 \]
So the correct response is:
x equals negative 4.